Pelatihan Pembuatan Miniatur Kapal Nelayan Berbahan Fiber-Reinforced Plastic (FRP) bagi Siswa SMKN 1 Tambakboyo Tuban - Radianto, Denny Oktavina; Sumardiono, Sumardiono; Suhardjito, Gaguk; Wibawa, I Putu Arta; Soelistijono, Rachmad Tri (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Community service entitled Training on Making Miniature Fishing Boats Made of Fiber-Reinforced Plastic (FRP) for Students of SMKN 1 Tambakboyo, Tuban City With the background of the existence of Tuban City as one of the coastal areas which is still trying to develop its community resources in the marine sector. Several vocational schools in Tuban have opened shipping and shipping engineering majors. Generally, these SMK students are taught how to operate supporting equipment for repair or management of ship transportation according to industrial needs. The purpose of this community service is to provide skills to students, especially at SMKN 1 Tambakboyo Tuban on how to make miniature fishing boats made of Fiber-Reinforced Plastic (FRP). Through shipbuilding skills that are more efficient in operation, it is hoped that the next generation of fishermen will have economic competitiveness because they are able to produce and use ships as efficient fishing facilities. The training was conducted online on Sunday 27 September 2020. The number of training participants was 53 participants from several schools in Tuban.